On the exponential decay of vibrations of damped elastic media - Vakarchuk, M. B.; Vakarchuk, S. B. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
Exact inequalities of the Kolmogorov type are obtained in Hardy Banach spaces for functions of one complex variable analytic in the unit disk and functions of two complex variables analytic in the unit bidisk. We also present applications of these inequalities to problems of the theory of approximation of analytic functions of one and two complex variables.